Studies on Mutravaha Srotadusti W.S.R. to Lower Urinary Tract Infection (AYUSHDHARA, 2022)
In Ayurveda, the term Srota has several meanings, but it primarily denotes channels or vessels or any hollow space. Although the total macro and micro channels within the human body are actually countless, thirteen important types of channels are described in all major compendiums. One such important channel is Mutravaha Srota. All the primary diseases of Mutra like Mutrakricchra, Mutraghata, Ashmari or Prameha are the consequences of Mutravaha Srotadusti. Thus in respect to modern science, Mutravaha Srotadusti can be correlated with all types of lower urinary tract infections and the diseases produced as its consequence. Aims and Objectives: The present study was carried out to evaluate the concept of Mutravaha Srota and Mutravaha Srotadusti in terms of lower UTI as well as to evaluate the efficacy of the selected drug Gokshur to combat the situation. Materials & Methods: In the selected 50 patients of lower UTI with features of Mutravaha Srotadusti, based on the inclusion and exclusion criteria, Gokshur Churna was administered in stipulated dose (5 gram twice daily with warm water) for 21 days. Observation: The subjective parameters of Mutravaha Srotadusti are present in maximum number of patients of lower UTI. The result also reveals the significant efficacy of the selected drug i.e., Gokshur Chruna to combat Mutravaha Srotadusti and lower UTI with ‘p’ value